CO2 Monitoring and Background Mole Fraction at Zhongshan Station, Antarctica - Yulong Sun; Lingen Bian; Jie Tang; Zhiqiu Gao; Changgui Lu; Russell C. Schnell (Atmosphere, 2014)
Background CO2 mole fraction and seasonal variations, measured at Zhongshan station, Antarctica, for 2010 through 2013, exhibit the expected lowest mole fraction in March with a peak in November. Irrespective of wind direction, the mole fraction of CO2 distributes evenly after polluted air from station operations is removed from the data sets. The daily range of average CO2 mole fraction in all four seasons is small. The monthly mean CO2 mole fraction at Zhongshan station is similar to that of other stations in Antarctica, with seasonal CO2 amplitudes in the order of 384–392 µmol∙mol−1. The annual increase in recent years is about 2 µmol∙mol−1∙yr−1. There is no appreciable difference between CO2 mole fractions around the coast of Antarctica and in the interior, showing that CO2 observed in Antarctica has been fully mixed in the atmosphere as it moves from the north through the southern hemisphere.